Rosmarinic acid inhibits proliferation and migration, promotes apoptosis and enhances cisplatin sensitivity of melanoma cells through inhibiting ADAM17/EGFR/AKT/GSK3β axis. Issue 1 (1st January 2021) - Huang, Lin; Chen, Jiangyan; Quan, Jin; Xiang, Debing
ABSTRACT: Rosmarinic acid (RA), a naturally occurring polyphenolic compound, exerts multiple biological properties including anti-cancer. The metalloprotease, a disintegrin and metalloproteinase 17 (ADAM17), can activate ligands of the epidermal growth factor receptor (EGFR) and contribute to tumor progression. We aimed to investigate whether RA could exhibit anti-cancer effects in melanoma cells through down-regulating ADAM17. The human melanoma A375 cells were exposed to RA, then cell viability, migration, invasion, apoptosis, melanin content and the expression of ADAM17/EGFR/AKT/GSK3β were evaluated. The viability of cells exposed to RA in the presence of cisplatin (Cis) was measured by CCK-8. Cells were overexpressed with ADAM17 in the absence or presence of RA and ADAM17 inhibitor (TACE prodomain; TPD) co-treatment, then the above cellular processes were also observed. Results showed that A375 cells treated with RA showed significant lower cell viability, proliferation, migrative and invasive abilities, melanin content and expression of related proteins including MMP2 and MMP9, compared with normal cells. RA enhanced the ratio of TUINEL-positive cells, the expression of pro-apoptotic proteins, but reduced Bcl-2 expression. RA co-treatment increased the inhibitory effect of Cis on cell viability. RA inhibited the expression of ADAM17/EGFR/AKT/GSK3β, which was further suppressed by TPD. Moreover, ADAM17 overexpression blocked all the effects of RA whereas TPD treatment generated an opposite function. In conclusion, RA exerted obvious inhibitory effect on melanoma cell proliferation, migration and invasion, but promotive effect on cells apoptosis. Addition, the showing of this characteristic of RA may rely on inhibiting the expression of ADAM17/EGFR/AKT/GSK3β axis. Abstract : uf0001